2022
DOI: 10.3390/molecules27103246
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Processing on Bioactive Compounds and Biological Activities of Sorghum Grains

Abstract: Sorghum is ranked the fifth most commonly used cereal and is rich in many kinds of bioactive compounds. Food processing can affect the accumulation and decomposition of bioactive compounds in sorghum grains, and then change the biological activities of sorghum grains. The present review aims to analyze the effects of processing technologies on bioactive compounds and the biological activities of sorghum grains. Decortication reduces the total phenols, tannins, and antioxidant activity of sorghum grains. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The concentrations of various bioactive compounds in different varieties of millets are summarized in Table 1 . For instance, sorghum grain's phenolic acids include caffeic acid, p-coumaric acid, ferulic acid, sinapic acid, chlorogenic acid, protocatechuic acid, p-hydroxybenzoic acid, vanillic acid, salicylic acid, gallic acid, and syringic acid [ 48 ]. Flavonoids are abundant in the outer layers, which include anthocyanins, dihydro flavanol, flavones, flavanones, flavanols, flavanols, and isoflavones, with anthocyanin s being the predominant compound [ 48 ].…”
Section: An Overview Of Bioactive Compounds Of Milletsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of various bioactive compounds in different varieties of millets are summarized in Table 1 . For instance, sorghum grain's phenolic acids include caffeic acid, p-coumaric acid, ferulic acid, sinapic acid, chlorogenic acid, protocatechuic acid, p-hydroxybenzoic acid, vanillic acid, salicylic acid, gallic acid, and syringic acid [ 48 ]. Flavonoids are abundant in the outer layers, which include anthocyanins, dihydro flavanol, flavones, flavanones, flavanols, flavanols, and isoflavones, with anthocyanin s being the predominant compound [ 48 ].…”
Section: An Overview Of Bioactive Compounds Of Milletsmentioning
confidence: 99%
“…For instance, sorghum grain's phenolic acids include caffeic acid, p-coumaric acid, ferulic acid, sinapic acid, chlorogenic acid, protocatechuic acid, p-hydroxybenzoic acid, vanillic acid, salicylic acid, gallic acid, and syringic acid [ 48 ]. Flavonoids are abundant in the outer layers, which include anthocyanins, dihydro flavanol, flavones, flavanones, flavanols, flavanols, and isoflavones, with anthocyanin s being the predominant compound [ 48 ]. Sorghum grains contain varying amounts of xanthophylls such as lutein and zeaxanthin, with lutein, zeaxanthin, and β-carotene being the most frequently found [ 49 ].…”
Section: An Overview Of Bioactive Compounds Of Milletsmentioning
confidence: 99%
“…Despite to process advantages, the most common traditional technique of processing sorghum grain consumes time. For instance, a recent paper on sorghum germination indicated that nutritional improvements were seen after 7 days of the procedure (Kayisoglu et al ., 2024), confirming, to literature as outlined sorghum processing issues addressing the inefficiency of germ removal and time‐consuming, which can leads to decreased shelf life and discolouration, ultimately affecting the quality and appearance of the final product (Li et al ., 2022; Khoddami et al ., 2023), Hence, it is necessary to involve more effective time processing, as the HFTU procedure provides. Furthermore, the modern grain processing equipment prioritises environmental protection requirements and operational safety, ensuring a people‐centric and sustainable approach (Lovegrove et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Soaking, which is a preliminary step to mechanical and biological processing of cereals, can lead to the modifications of grains texture and the release of water-soluble compounds. Many studies showed soaking significantly decreased total phenols and minerals, while others revealed an increase in antioxidant activity (Li et al, 2022). Germination results in the degradation of macronutrients, reduction of anti-nutritional factors, and increase of the bioactive potential of sorghum grains (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Germination results in the degradation of macronutrients, reduction of anti-nutritional factors, and increase of the bioactive potential of sorghum grains (Liu et al, 2019). Studies on fermentation revealed contradictory effects on total phenol contents and total flavonoid contents (Li et al, 2022). A review done by Taylor and Duodu (2015) showed that biological processing methods also affect the antioxidant potential of sorghum and millet grains.…”
Section: Introductionmentioning
confidence: 99%